Kegiatan Mengaji secara Terbatas di LPQ Wardatul Ishlah dengan Menerapkan Protokal Kesehatan sebagai Bentuk Moderasi Beragama pada Masa Pandemi COVID-19 - Sanidah, Sanidah; Rofiki, Imam (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The government has tried to make various efforts to suppress the spread of COVID-19, including by making health protocols in various life activities in the community. Learning activities at the Wardatul Ishlah Al-Qur'an Education Institute located at the Wardatul Ishlah Mosque resulted in large crowds, while in the pandemic era this was very much against health protocol in order to prevent and suppress the spread of COVID-19. However, the recitation of the holy Qur’an is not an easy activity to leave, because the activity is a fairly primary activity and is not easy to just take a day off. Due to the conflict between the two interests, namely the interests of health and the interests of religion, at LPQ Wardatul Ishlah, they are looking for a middle way and applying the concept of religious moderation so that reciting activity can still be carried out while still complying with health protocol.